Peribacillus castrilensis sp. nov.: A Plant-Growth-Promoting and Biocontrol Species Isolated From a River Otter in Castril, Granada, Southern Spain - Rodríguez, Miguel; Reina, José Carlos; Sampedro, Inmaculada; Llamas, Inmaculada; Martínez-Checa, Fernando (Frontiers in Plant Science, 2022)
A strictly aerobic, chemoheterotrophic, endospore-forming, Gram-positive, rod-shaped bacterial strain N3T was isolated from the feces of a river otter in Castril (Granada, southern Spain). It is halotolerant, motile, catalase-, oxidase-, ACC deaminase- and C4 and C8 lipase-positive. It promotes tomato plant growth and is able to reduce virulence in Erwinia amylovora CECT 222T and Dickeya solani LMG 25993T through the interference in their quorum sensing systems, although other antagonistic mechanisms could also occur. Phylogenetic analysis of the 16S rRNA gene sequence as well as phenotypic and phylogenomic analyses indicated that strain N3T is a novel species of the genus Peribacillus, with the highest 16S rRNA sequence similarity to Bacillus frigoritolerans DSM 8801T (99.93%) and Peribacillus simplex DSM 1321T (99.80%). Genomic digital DNA-DNA hybridization (dDDH) between strain N3T and Bacillus frigoritolerans DSM 8801T and Peribacillus simplex was 12.8% and 69.1%, respectively, and average nucleotide identity (ANIb), 67.84% and 93.21%, respectively. Genomic G + C content was 40.3 mol%. Its main cellular fatty acids were anteiso-C15:0 and iso-C15:0. Using 16S rRNA phylogenetic and in silico phylogenomic analyses, together with chemotaxonomic and phenotypic data, we demonstrated that type strain N3T (=CECT 30509T =LMG 32505T) is a novel species of genus Peribacillus and the name Peribacillus castrilensis sp. nov. is proposed.